Jalan Menuju Kemandirian Finansial Lembaga Pendidikan Islam Dengan Pendekatan Zero Capital - Novita Sari, Desi; Panca Putera, Rachmat (PT. LEMBAGA PENERBIT PENELITIAN NUSANTARA, 2025)
Financial independence remains a critical challenge for Islamic educational institutions, primarily due to their persistent reliance on external funding sources. Such dependency not only undermines financial stability but also constrains institutional autonomy and long-term sustainability. This article aims to conceptually examine pathways toward financial independence in Islamic educational institutions through a zero capital approach. Employing a qualitative library research design, this study critically analyzes scholarly books and peer-reviewed journal articles related to Islamic education management, social entrepreneurship, and non-profit organizational governance. The findings reveal that financial independence is not solely determined by the availability of financial capital, but rather by the institution’s capacity to optimize non-financial assets, including social capital, intellectual capital, and symbolic capital. The zero capital approach emerges as a transitional strategy that encourages the effective utilization of internal resources, competency-based productive innovation, and operational efficiency through digitalization. The novelty of this article lies in repositioning financial independence as a structural, asset-based process aligned with Islamic values, rather than as an instant outcome driven by monetary capital. This study contributes to the advancement of Islamic education management discourse and offers strategic insights for institutional leaders seeking sustainable financial independence under resource constraints.